"I wanted a skeleton … they brought a prince": A qualitative investigation of factors mediating the implementation of a Performance Based Incentive program in Malawi. (August 2018) - McMahon, Shannon A.; Muula, Adamson S.; De Allegri, Manuela
Abstract: While several evaluations have examined the extent to which performance based financing (PBF) programs induce changes in the quantity and quality of health services provided, less is known about the process of implementing PBF. We conducted a process evaluation of a PBF intervention in Malawi that focused on understanding moderators of program implementation. Informed by a seminal theory of implementation, we first created a timeline and taxonomy of key events in the program lifeline and then undertook 25 in-depth interviews with stakeholders including implementers, central-level ministry officials and district-level health staff. While seven "moderator categories" emerged in this study, two categories (program complexity and quality of delivery) proved especially crucial in terms of moderating implementation and sparking adaptations. Complexity refers primarily to the manner in which PBF requires that those implementing the program have business acumen and forecasting skills, which are often beyond the purview of a clinician's training and thus proved challenging. Regarding quality of delivery, the program struggled to issue rewards in a timely and adequate manner, which proved highly problematic as it undermined a bedrock feature of PBF. Adaptations and adaptability refers here to a program's ability to make changes; the program proved rigid in several respects although nimble in terms of adjusting the verification process (upon noticing revengeful behaviors in peer verification). This PBF program is unique in several respects and findings cannot be generalized to all PBF programs. Nevertheless, process evaluations that draw from or expand upon existing implementation theories can allow researchers to better disentangle complex programming. We hope that more process evaluations, which track both core elements and necessary adaptations of PBF implementation, can further advance understandings of why PBF implementation functions or fails within a given setting, thereby enhancing implementers' abilities to replicate facilitators and bypass barriers. Highlights: Most performance based financing (PBF) research examines outcome not process. We used expectation theory and a seminal implementation framework to study PBF in Malawi. Two key factors (complexity and quality of delivery) moderated implementation and sparked adaptations. PBF implementation requires business acumen- a skill that is not inherent among all clinicians. Timely reward issuance is a bedrock promise of PBF that must be met to stimulate success.